Identification and expression of microRNAs in european eels Anguilla anguilla from two natural sites with different pollution levels. (July 2019) - Bertucci, Anthony; Pierron, Fabien; Ye, Tao; Gonzalez, Patrice; Couture, Patrice; Baudrimont, Magalie
Abstract: MicroRNAs (miRNAs) are a class of small non-coding RNA that control multiple biological processes through negative post-transcriptional regulation of gene expression. Recently a role of miRNAs in the response of aquatic organisms to environmental toxicants emerged. Toxicant-induced changes in miRNA expression might then represent novel biomarkers to evaluate the health status of these organisms. In this study, we aimed to identify the miRNA repertoire in the liver of the European eel Anguilla anguilla and to compare their differential expression between a polluted site located in the Gironde Estuary and a pristine site in Arcachon Bay (France). A total of 299 mature miRNAs were identified. In polluted water, 19 miRNAs were up-regulated and 22 were down-regulated. We predicted that these differentially expressed miRNAs could target 490 genes that were involved in ribosome biogenesis, response to hormones, response to chemical and chromatin modification. Moreover, we observed only few examples (29) of negative correlation between the expression levels of miRNAs and their targets suggesting that, in the system studied, miRNAs might not only regulate gene expression directly by degrading mRNA but also by inhibiting protein translation or by regulating other epigenetic processes. This study is the first example of in situ investigation of the role of miRNAs in the response of a fish species to water quality. Our findings provide new insights into the involvement of epigenetic mechanisms in the response of animals chronically exposed to pollution and pave the way for the utilization of miRNAs in aquatic ecotoxicology. Graphical abstract: Image 1 Highlights: 299 MicroRNAs were characterized in the endangered European eel Anguilla anguilla. The expression levels of 41 microRNAs were altered in fish from a polluted site. Differentially expressed microRNAs might regulate important biological processes. Abstract : This work explores the repertoire of small non-coding RNAs (microRNAs) and its response to water pollution in the endangered European eel.